The politics of Apollonius Rhodius' Argonautica - Mori, Anatole, 1960- (Cambridge : Cambridge University Press, 2008)
Apollonius Rhodius'epic poem, the Argonautica, is one of the most important and influential literary productions of the Hellenistic period. This book shows how the retelling of a heroic adventure set in the generation before the Trojan War engages the political, religious, and ethical dynamics of its day by alluding to the real-world context of the early Ptolemaic dynasty as well as to poetic and other models. Through a hegemonic typology that ranges from the just and theocratic to the duplicitous and lawless, Apollonius characterizes the political heirs of Alexander the Great as pious, civilized rulers. This interpretation goes beyond previous studies by examining the political resonance of religious activity in the poem, and by relating these formulations (especially where they concern Apollonius'departures from his literary predecessors) to the ideological construction of Hellenic identity in third-century Egypt.
1, Introduction -- 2, The politics of Alexandrian poetry -- 3, Strife and restraint among the Argonauts -- 4, Sexual politics in Lemnos, Colchis, and Drepane -- 5, Piety, mediation, and the favor of the gods -- 6, The bones of Apsyrtus -- 7, Quid denique restat : Apollonius and Virgil
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: Apollónios Rhodský, -- 220 př. Kr.-140 př. Kr; 3. století př. Kr; Argonauti (mytologické postavy); řecký antický epos -- 3. století př. Kr; řecká antická poezie -- politické aspekty; literárněvědné rozbory; Argonauts (Greek mythology); Greek ancient epos -- 3rd century B.C.; Greek ancient poetry -- political aspects; literary criticism and history; e-knihy online; monografie; e-books online; monographs